Aptamer-incorporated hydrogels for visual detection, controlled drug release, and targeted cancer therapy - Liu, Jun (Anal Bioanal Chem, 2011)
Hydrogels are water-retainable materials, made from cross-linked polymers, that can be tailored to applications in bioanalysis and biomedicine. As technology advances, an increasing number of molecules have been used as the components of hydrogel systems. However, the shortcomings of these systems have prompted researchers to find new materials that can be incorporated into them. Among all of these emerging materials, aptamers have recently attracted substantial attention because of their unique properties, for example biocompatibility, selective binding, and molecular recognition, all of which make them promising candidates for target-responsive hydrogel engineering. In this work, we will review how aptamers have been incorporated into hydrogel systems to enable colorimetric detection, controlled drug release, and targeted cancer therapy.